Distribution of Thermus spp. in Icelandic Hot Springs and a Thermal Gradient - Kristjansson, Jakob K. (1983)
The growth range in nature of bacteria belonging to the genus Thermus was investigated by sampling 55 different hot springs in Iceland. The springs ranged in temperature from 32 to 99°C, and in pH from 2.1 to 10.1. Viable counts of Thermus spp. ranging from 10 to 10(4) CFU/100 ml of spring water were found in 27 of the springs sampled. The temperature range for these bacteria was found to be 55 to 85°C, and the pH range was from about 6.5 to above 10. Thermus spp. were found in springs containing up to 1 mM dissolved sulfide and having conductivity up to 2,000 μS/cm. The distribution of Thermus spp. in a hot spring thermal gradient was also investigated and found to agree well with the overall distribution in individual springs.